Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm struggling to understand the correct interpretation of conditional expectation of the form $$ E[X \mid Y, Z ]. $$ I know that $E[X \mid Y]$ is itself a random variable $f(y) = E[X \mid Y=y]$. Does this mean that the above is a random variable $g(Y,Z)$ where $$g(y,z) = E[X \mid Y = y, Z = z]\ ?$$

On the other hand, $E[X \mid Y,Z ]$ is nothing but $E[X \mid \sigma(Y,Z)]$. Clearly $\sigma(Y) \subseteq \sigma(Y,Z)$, so $E[X\mid Y,Z]$ is a constant when conditioning on some event $\{Y=y\} \in \sigma(Y)$, which seems to contradict the above interpretation as a r.v. depending on $Y$ and $Z$.

What am I missing here?

share|cite|improve this question
If $g(y,z)=\mathbb E(X\mid Y=y\ \&\ Z=z)$, then $\mathbb E(X\mid Y,Z)$ is the random variable $g(Y,Z)$ (not $g(y,z)$, which is not a random variable). – Michael Hardy Oct 8 '12 at 17:16
Thanks, I hope it's correct now. – somebody Oct 8 '12 at 17:21
Why should $E[X|Y=y,Z]$ be a constant? It is a function of the r.v. $Z$. – emrea Oct 8 '12 at 17:25
$E[X|Y,Z]$ will be a constant only when both $Y$ and $Z$ are instantiated/observed. – emrea Oct 8 '12 at 18:21
It might be misleading to say that $g(Y,Z)$ always conditions on both $Y$ and $Z$. No, it doesn't have to. The correct statement is this: if you condition it on both $Y$ and $Z$, it becomes a constant; if you condition it on $Y$ it becomes a function of r.v. $Z$; if you condition it on $Z$ it becomes a function of r.v. $Y$. – emrea Oct 9 '12 at 16:20

A simple example might help: assume that $X=Y+Z$ where the random variables $Y$ and $Z$ are integrable and independent.

Then $\mathbb E(X\mid Y,Z)=X$ because $X=Y+Z$ is $\sigma(Y,Z)$-measurable.

On the other hand, $Y$ is $\sigma(Y)$-measurable hence $\mathbb E(Y\mid Y)=Y$, and $Z$ is independent of $\sigma(Y)$ hence $\mathbb E(Z\mid Y)=\mathbb E(Z)$. Thus, $\mathbb E(X\mid Y)=\mathbb E(Y\mid Y)+\mathbb E(Z\mid Y)=Y+\mathbb E(Z)$.

Likewise, $\mathbb E(X\mid Z)=\mathbb E(Y)+Z$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.